Biodiversity and Distribution of Squat Lobster of the Family Munididae Ahyong, Baba, Macpherson & Poore, 2010 (Crustacea: Decapoda: Anomura: Galatheoidea) in Some Areas in Indonesia - Ernawati Widyastuti; Suyarso (Advanced Research in Biological Science Vol. 6, 2023)
This paper intends to review the presence of squat lobster from the family Munididae and their distribution in Indonesian waters. Squat lobsters of the family Munididae were recorded from Indonesian waters with 15 genera and 72 species. It counts 15.6% of the world species. Most of the squats lobster in Indonesia were obtained from international expeditions conducted since 1873 to the most recent in 2018. These squat lobsters live in shallow to deep waters. In Indonesian waters, they were found in the Sunda Strait, Hindian Ocean, Java Sea, Makasar Strait, Sulawesi Sea, Maluku Sea, Seram Sea, Banda Sea and Arafura Sea.